Children's Racial Categorization in Context - Pauker, Kristin (Child Dev Perspect, 2015)
The ability to discriminate visually based on race emerges early in infancy: 3-month-olds can perceptually differentiate faces by race and 6-month-olds can perceptually categorize faces by race. Between ages 6 and 8 years, children can sort others into racial groups. But to what extent are these abilities influenced by context? In this article, we review studies on children's racial categorization and discuss how our conclusions are affected by how we ask the questions (i.e., our methods and stimuli), where we ask them (i.e., the diversity of the child's surrounding environment), and whom we ask (i.e., the diversity of the children we study). Taken together, we suggest that despite a developmental readiness to categorize others by race, the use of race as a psychologically salient basis for categorization is far from inevitable and is shaped largely by the experimental setting and the greater cultural context.